Headache following Spinal Anaesthesia: A Review on Recent Update - Alam, MR; Raheen, MR; Iqbal, KM; Chowdhury, MRA (Journal of Bangladesh College of Physicians and Surgeons, 2011)
Central neuraxial block is an extensively implemented technique in anaesthetic practice. Spinal dural punctures occur deliberately in spinal anaesthesia and inadvertently during attempting epidural blocks. The incidence of disabling headache following dural perforation ranges from 0.3 to 20% in spinal anaesthesia and may be upto 70% after accidental dural puncture in epidural anaesthesia. Decreased CSF volume causing reduced pressure and responsive cerebral venodilation due to CSF leakage are deduced as the prime reasons for this post-dural puncture headache (PDPH). The headache is selflimiting and 88% of it resolves without any interference, if not superimposed by any pre-existing or a de novo complication. Anaesthesiologists have been perpetually active in reducing the incidence. Int’l and regional working groups have advocated the use of fine gauge pencil-point needles, delicate bevel orientation techniques, some new drug regimens and various useful and effective measures for the treatment and prevention of PDPH. This review considers some contentious aspects of pathogenesis, treatment and prevention of PDPH and summarises the recommendations incorporated with updated guidelines of American Society of Regional Anesthesia (ASRA) and Society for Obstetric Anesthesia & Perinatology (SOAP) for the management of PDPH. DOI: 10.3329/jbsp.v29i1.7169 J Bangladesh Coll Phys Surg 2011; 29:32-40